2009
DOI: 10.1111/j.1468-3083.2009.03353.x
|View full text |Cite
|
Sign up to set email alerts
|

Smoking, sun exposure, number of nevi and previous neoplasias are risk factors for melanoma in older patients (60 years and over)

Abstract: Tobacco smoking is an independent risk factor for cutaneous melanoma in the elderly. Intense (both acute and chronic) sun exposure and constitutional features, such as tumor susceptibility (NMSC, non-cutaneous neoplasias, and multiple nevi) are also associated with melanoma risk. All these factors should help to better design educational campaigns in older people.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
25
0
15

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(45 citation statements)
references
References 49 publications
5
25
0
15
Order By: Relevance
“…Our results are also consistent with two cohort studies that stratified by smoking status and reported gender-specific results [3,6]. To date, only one case-control study has reported increased risk of incident melanoma associated with smoking [16].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our results are also consistent with two cohort studies that stratified by smoking status and reported gender-specific results [3,6]. To date, only one case-control study has reported increased risk of incident melanoma associated with smoking [16].…”
Section: Discussionsupporting
confidence: 93%
“…Sun exposure, especially sunburns is the major risk factor for melanoma; other established risk factors include age, race, and inherited susceptibility. Fourteen studies have examined the association between smoking and risk of melanoma; all but one of these studies reported at least a small inverse relationship with current smoking [3,[5][6][7][8][9][10][11][12][13][14][15][16][17]. However, none of these studies examined the risk of melanoma-mortality, only one cohort study included more than 300 cases, and none presented results separately for men and women in the general population [6].…”
Section: Introductionmentioning
confidence: 98%
“…[26] Sigara, yo¤un günefl maruziyeti, 50'nin üzerinde melanositik nevü-sün varl›¤› ve geçirilmifl habis hastal›k 60 yafl üstündeki melanomun risk faktörleridir. [27] Bütün melanom tipleri yaflla artar, 60 yafl üzerinde günefllenme al›flkanl›¤› varsa lentigo malin melanom görülme s›kl›¤› özellikle artar. Dü-zensiz s›n›rl›, asimetrik kahverengi makül fleklinde olup, nodülleflmesi yay›lmaya iflaret eder.…”
Section: Deri Tümörleriunclassified
“…Lifestyle factors were highly influential [31].check Heat related illnesses are more likely in older adults exposed to excessive warm sunlight and elevated temperature due to the combination of multimorbidity, impaired auto regulatory mechanisms, behaviours and multiple medications which may impair their homeostatic mechanisms [37].…”
Section: Community Dwelling and Institutionalised Older Adults Evidencementioning
confidence: 99%
“…In those older than 60 years, chronic sun exposure, smoking, large number of melanocytic naevi and a history of prior neoplasia including NMSC are risk factors for CMM as is tumour susceptibility and intense sun exposure [31].…”
Section: Malignant Melanoma (Mm)mentioning
confidence: 99%